Amgen : launching Repatha - Calkins, Tim (SAGE Knowledge. Cases., 2017)
In March 2015, Amgen is preparing for the launch of Repatha, a new molecule that has demonstrated a remarkable ability to treat high cholesterol. Through a series of clinical trials, Amgen has proven that the molecule is both safe and effective for patients with high cholesterol. It also is effective for patients with familial hypercholesterolemia, a difficult-to-treat population that has exceptionally high levels of cholesterol. Amgen expects the FDA to approve the molecule before the end of the year. Now, the Repatha team has to develop a revenue forecast.